2011
DOI: 10.2183/pjab.87.81
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mechanisms of renoprotection against progressive glomerulosclerosis

Abstract: In this review, I introduce the strategy developed by our laboratory to explore the mechanisms of renoprotection against progressive glomerulosclerosis leading to renal death. First, I describe the experimental rat model in which disturbances of vascular regeneration and glomerular hemodynamics lead to irreversible glomerulosclerosis. Second, I discuss the possible mechanisms determining the progression of glomerulosclerosis and introduce a new imaging system based on intravital confocal laser scanning microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In contrast to the techniques used in previous micropuncture studies, intravital microscopy is considered less invasive because it involves fewer manipulations of the site of interest, such as the placement of the kidney into a Lucite cup and the insertion of micropipettes. The baseline snGFR determined by multiphoton microscopy was within a similar range to that reported previously for MFW rats based on micropuncture experiments 2,4,5,17,28 . Similarly, the infusion of angiotensin II led to a significant decrease in the snGFR in control rats 23,29 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast to the techniques used in previous micropuncture studies, intravital microscopy is considered less invasive because it involves fewer manipulations of the site of interest, such as the placement of the kidney into a Lucite cup and the insertion of micropipettes. The baseline snGFR determined by multiphoton microscopy was within a similar range to that reported previously for MFW rats based on micropuncture experiments 2,4,5,17,28 . Similarly, the infusion of angiotensin II led to a significant decrease in the snGFR in control rats 23,29 .…”
Section: Discussionsupporting
confidence: 86%
“…The baseline snGFR determined by multiphoton microscopy was within a similar range to that reported previously for MFW rats based on micropuncture experiments. 2,4,5,17,28 Similarly, the infusion of angiotensin II led to a significant decrease in the snGFR in control rats. 23,29 It has been suggested that the preferential constriction of the afferent versus the efferent arteriole and a concomitant reduction in the net renal plasma flow account for the effect of angiotensin II on the snGFR.…”
Section: Discussionmentioning
confidence: 88%
“…Using apolipoprotein E knockout mice, our previous study demonstrated that RAS activation was involved in dyslipidemia-mediated renal injuries 14. Accordingly, after treatment with a RAS inhibitor or lipid-lowering drugs, the progression of glomerulosclerosis was attenuated 15, 16. These findings suggested the existence of synergistic effects of RAS activation and lipid disorders in renal injuries.…”
Section: Discussionmentioning
confidence: 93%